CRISPR/Cas9 and iPSC-Based Therapeutic Approaches in Alzheimer’s Disease - Ivana Raffaele; Giovanni Luca Cipriano; Ivan Anchesi; Salvatore Oddo; Serena Silvestro (Antioxidants)
Alzheimer’s disease (AD), the leading cause of dementia, remains poorly understood despite decades of intensive research, which continues to hinder the development of effective treatments. As a complex multifactorial disorder, AD lacks a cure to halt the progressive neurodegeneration, and the precise mechanisms underlying its onset and progression remain elusive, limiting therapeutic options. Due to the challenges of studying neuronal cells in vivo, technologies such as clustered regularly interspaced short palindromic repeats/CRISPR-associated protein 9 (CRISPR/Cas9) and human-induced pluripotent stem cells (hiPSCs) are key for identifying therapeutic targets, although they face technical and ethical hurdles in their early stages. CRISPR/Cas9 and hiPSCs are promising for disease modeling and therapy, but off-target effects and the complexity of gene editing in the brain limit their use. CRISPR technology enables specific genetic modifications in key AD-related genes, such as APP, PSEN1, PSEN2, and APOE, providing valuable insights into disease mechanisms. iPSC-derived neurons, astrocytes, microglia, and 3D organoids can recapitulate key aspects of human AD pathology, but they do not fully replicate the complexity of the human brain, limiting clinical applicability. These technologies advance studies of amyloid processing, tau aggregation, neuroinflammation, and oxidative stress, yet translating them into clinical therapies remains challenging. Despite the promise of CRISPR/Cas9 and iPSCs for precision medicine, gaps in knowledge about their long-term safety and efficacy must be addressed before clinical implementation.